Two new species of Ozothamnus (Asteraceae: Gnaphalieae) from Australia - Schmidt-Lebuhn, Alexander N.; Puttock, Christopher F.; Davis, Robert W.; Wege, Juliet (Phytotaxa, 2018)
Two new species of shrubs endemic to western and central Australia, respectively, are described as Ozothamnus vespertinus R.W.Davis, Wege & Schmidt-Leb. and O. filifolius Puttock. A dichotomous key to the species of Ozothamnus and Cassinia known from Western Australia and the Northern Territory is provided.